Іmpact of innovation on economic growth in the Baltic Sea region (by way of example of studies for Latvia and Denmark) - Rukon, Ataul Karim (Збірник наукових праць Черкаського державного технологічного університету. Серія: Економічні науки, 2016)
The theses provide aspects of the impact of innovation on the country’s economic growth. The features of the innovation development of the Baltic Sea economies (by way of example of studies for Latvia and Denmark), namely, a global index of innovation in the countries, are examined. The influence of innovation costs of the countries on economic development (gross domestic product) is studied. The areas of innovation development to enhance the competitiveness of the Baltic Sea economies are suggested